ТЕОРЕТИЧЕСКОЕ ИССЛЕДОВАНИЕ ВЛИЯНИЯ КВАНТОВОГО ОГРАНИЧЕНИЯ НА ЭНЕРГЕТИЧЕСКИЙ СПЕКТР ПОЛУПРОВОДНИКОВЫХ СФЕРИЧЕСКИХ КВАНТОВЫХ ТОЧЕК С ИСПОЛЬЗОВАНИЕМ ЧАСТИЦЫ В МОДЕЛИ ЛОВУШКИ - Корабоев, К.А.; Сапаев, У.К. (SCIENCE and SOCIETY, 2022)
Using the particle model is studied in the trap, the effect of quantum limitation on the energy spectrum of spherical quantum dots CdSe, GaP, and GaAs. The energy levels of the free electrons in the conduction band and the holes in the valence band at the quantum dots have been shown to be discrete. It has also been shown that the energy between the two levels depends on the measurement of the quantum dots and increases with decreasing the size of the quantum dots. Our results show that as the radius of the limit point increases, the energy decreases, but never the zero mark.
Keywords: Schrödinger equation; quantum dot; semiconductor; quantum particle in trap; electron and holes